Nursing and medical contribution to Defence Healthcare Engagement: initial experiences of the UK Defence Medical Services. Issue 3 (4th June 2019) - Bowley, Douglas M; Lamb, D; Rumbold, P; Hunt, P; Kayani, J; Sukhera, A M
Abstract : Introduction: The WHO Constitution enshrines '… the highest attainable standard of health as a fundamental right of every human being .' Strengthening delivery of health services confers benefits to individuals, families and communities, and can improve national and regional stability and security. In attempting to build international healthcare capability, UK Defence Medical Services (DMS) assets can contribute to the development of healthcare within overseas nations in a process that is known as Defence Healthcare Engagement (DHE). Methods: In the first bespoke DMS DHE tasking, a team of 12 DMS nurses and doctors deployed to a 1000-bedded urban hospital in a partner nation and worked alongside indigenous healthcare workers (doctors, nurses and paramedical staff) during April and May 2016. The DMS nurses focused on nursing hygiene skills by demonstrations of best practice and DMS care standards, clinical leadership and female empowerment. A Quality Improvement Programme was initiated that centred on hand hygiene (HH) compliance before and after patient contact, and the introduction of peripheral cannula care and surveillance. Results: After a brief induction on the ward, it was apparent that compliance with HH was poor. Peripheral cannulas were secured with adhesive zinc oxide tape and no active surveillance process (such as venous infusion phlebitis (VIP) scoring) was in place. After intensive education and training, initial week-long audits were undertaken and repeated after a further 2 weeks of training and coworking. In the second audit cycle, HH compliance had increased to 69% and VIP scoring compliance to 99%. In the final audit cycle, it was noted that nursing compliance with HH (75/98: 77%) was significantly higher than the doctors' HH compliance (76/200: 38%); p<0.0001. Conclusions: DHE is a long-term collaborative process based on the establishment and development of comprehensive relationships that can help transform indigenous healthcare services towards patient-centred systems with a focus on safety and quality of care. Short deployments to allow clinical immersion of UK healthcare workers within indigenous teams can have an immediate impact. Coworking is a powerful method of demonstrating standards of care and empowering staff to institute transformative change. A multidisciplinary group of Quality Improvement Champions has been identified and a Hospital Oversight Committee established, which will offer the prospect of longer term sustainability and development.